Thyroid Scintigraphy Findings in 234 Hyperthyroid Cats Before and After Radioiodine Treatment - Lisa Stammeleer; Pilar Xifra; Sara I. Serrano; Eva Vandermeulen; Sylvie Daminet; Mark E. Peterson (Animals)
Thyroid scintigraphy is a key tool for diagnosing and staging hyperthyroidism in cats, but follow-up scintigraphic studies after radioiodine treatment are limited. This multicentric study evaluated 99mTc-pertechnetate scintigraphy findings in 234 hyperthyroid cats before and 6 months after radioiodine treatment. Based on serum T4 and TSH concentrations, 165 (70.5%) became euthyroid, 54 (23.1%) had subclinical hypothyroidism, and 15 (6.4%) developed overt hypothyroidism. On post-treatment scintigraphy, all cats showed reduced size and radionuclide uptake of “hot” thyroid nodules. Of 99 cats with unilateral nodules, 60 (61%) recovered function in the contralateral lobe. Among 135 cats with bilateral nodules, both lobes remained visible in 108 (80%). Persistent “hot” nodules with high thyroid/salivary (T/S) ratios or thyroidal pertechnetate uptake (TcTU) occurred in 26 (11%) cats, all of which were euthyroid. Conversely, 24 (10.4%) cats had minimal or absent thyroid tissue with 17 (71%) being hypothyroid, but seven (29%) were euthyroid. As a diagnostic test for iatrogenic hypothyroidism, TcTU showed the highest sensitivity (62.3), with the T/S ratio (7.3) and background-corrected T/S ratio (30.4) being much lower (p < 0.01). While follow-up scintigraphy aids in assessing thyroid tumor destruction and residual function, its diagnostic utility for differentiating euthyroidism and hypothyroidism is limited, especially for cats with mild (subclinical) hypothyroidism.